2006
DOI: 10.1136/jcp.2005.031963
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase IIα in Wilms’ tumour: gene alterations and immunoexpression

Abstract: Background: Topoisomerase IIa (topoIIa) is an essential enzyme gene in regulating DNA structure and cell proliferation and is encoded by the TOP2A . Using cDNA microarray analysis, TOP2A has been reported to be one of the top genes overexpressed in Wilms' tumour. Aim: To evaluate the role of TopoIIa in Wilms' tumorigenesis and its prognostic value. Methods: TOP2A gene copy numbers were determined using the fluorescence in situ hybridisation technique, and protein expression levels of TopoIIa by immunostaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…On the other hand, in two microarray expression studies, TOPO-II was found to exhibit high expression in WT and was even suggested to be related to the chemosensitivity of the tumor 15,16 . In a recent publication, TOPO-II was likewise found to be overexpressed (but in anaplastic WT samples) and its increased expression correlated with WT tumor aggressiveness 17 . TOPO-II has been proposed as a diagnostic marker distinguishing mesoblastic nephromas from Wilms' tumors 15 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in two microarray expression studies, TOPO-II was found to exhibit high expression in WT and was even suggested to be related to the chemosensitivity of the tumor 15,16 . In a recent publication, TOPO-II was likewise found to be overexpressed (but in anaplastic WT samples) and its increased expression correlated with WT tumor aggressiveness 17 . TOPO-II has been proposed as a diagnostic marker distinguishing mesoblastic nephromas from Wilms' tumors 15 .…”
Section: Discussionmentioning
confidence: 99%
“…TOP2A has been implicated as a marker of poor prognosis in numerous malignancies, including breast, renal cell, hepatocellular, prostate, and colorectal carcinomas [43,[45][46][47][48][49][50][51]. In addition, TOP2A has been reported to be a sensitive and specific marker for actively proliferating cells in colorectal carcinoma [44].…”
Section: Discussionmentioning
confidence: 99%
“…Microvessel densities were assessed as the vessel area normalized to total tissue area. Nuclear expression for FosB, c-Jun, and C/EBPh were quantified as the percentage of positive nuclei as previously described (22). Color-specific thresholds were used to determine brown (positive) and blue (negative) nuclei within the outlined areas of interest and to calculate the ratio of positively stained nuclei to all nuclei and expressed as a percentage (nuclear index).…”
Section: Methodsmentioning
confidence: 99%